The effect of Dental Aesthetical to Socialphysco on Teenagers (The study to make and female Public Senior High School in Palembang City) - Mujiyati, Mujiyati (Poltekkes Kemenkes Yogyakarta, 2021)
The increasing of worst maloclusi influence the improvement of status soscialphysco as the result the Dental Aesthetic. This Research aims to analize the effect of aesthetical dental characteristic to the status on the Teenagers Socialphysco Generally to the public Senior High School in Palembang. This Research design uses ‘cross sectional’. The population on this Research is the whole public Senior High School in Palembang which consist of 22 schools. The Sampling Research is consist of seven selected schools based on with drawing sampling methode namely ‘purposive stratified random sampling’ the names of the seven school are. The public Senior High School 4 Plaju, 9 Kertapati, 10 Ilir Barat I, 11 Ilir Barat I, 12 Gandus, 15 Ilir Timut I, and 19 Jakabaring. From the seven school above we have got 325 respondents and the result analysis shows that there is influence ‘Aesthetic Component’ to the status soscialphysco, sosial, physcologic and aesthetic on the male and female student in Palembang, and there is the effect ’Dental Health Component’ namely to the status of socialphyscoand aethetic. The conclusion is the majority of the respondent in this Research is the male and female students who need alitle Treatment from Aesthetic Component with the number of 105 person (the persontage of 32,4%) and the male of female students who has calculus dent are 210 person (the persontage of 64,6%). The advice Research is the male of female students is Palembang better to give attention to their teeth and mouth, aspecially in doing the Treatment maloclusi and also to take care to the cleanliness of their teeth and mouth.